2019
DOI: 10.1097/mpa.0000000000001330
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Appropriate Use of Pancreatic Enzyme Replacement Therapy and Symptomatic Response in Pancreatic Cancer Patients

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
(25 reference statements)
0
31
2
6
Order By: Relevance
“…Patients who were taking their enzymes with meals, rather than before or afterwards, were more likely to gain weight (p=0.022) and demonstrate less maldigestion (p=0.003) and less steatorrhoea (p=0.04) compared with those not taking PERT correctly. 93 The high incidence of incorrect timing is an important consideration when analysing data from studies assessing the clinical response to PERT, especially when data are collected retrospectively. Statement 3.2: Treatment with PERT improves QoL in patients with PEI (grade 1C; 100% agreement) While PERT is useful for treating PEI, studies that address whether it has a positive effect on the QoL of those taking it have been of variable quality.…”
Section: Aetiology Of Peimentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who were taking their enzymes with meals, rather than before or afterwards, were more likely to gain weight (p=0.022) and demonstrate less maldigestion (p=0.003) and less steatorrhoea (p=0.04) compared with those not taking PERT correctly. 93 The high incidence of incorrect timing is an important consideration when analysing data from studies assessing the clinical response to PERT, especially when data are collected retrospectively. Statement 3.2: Treatment with PERT improves QoL in patients with PEI (grade 1C; 100% agreement) While PERT is useful for treating PEI, studies that address whether it has a positive effect on the QoL of those taking it have been of variable quality.…”
Section: Aetiology Of Peimentioning
confidence: 99%
“…101 These data were supported by a survey of 262 patients, which demonstrated that patients consuming PERT throughout meals experienced fewer abdominal symptoms and more weight gain compared with patients who consumed PERT before or after meals. 93 Statement 4.4: If capsules cannot be swallowed, they should be opened, placed on an acidic puree and swallowed at intervals throughout the meal, and the mouth should be rinsed with cool water to prevent ulceration (GPP; 97% agreement) Some patients are unable to swallow capsules. In those circumstances, the capsules can be opened and the contents taken on a spoonful of cold acidic food, such as fruit puree, apple sauce, jam or fruit yoghurt and swallowed immediately.…”
Section: Management Of Pei Statement 41mentioning
confidence: 99%
“…The correct use of PERT remains a challenge for physicians dealing with EPI. In a recent survey on the appropriate use of PERT in patients with pancreatic cancer, it was observed that an appropriate prescription occurred in approximately 2/3 of patients, with 65% of them reporting compliance to therapy in terms of correct timing and modality of administration, confirming lack of awareness about PERT in the oncologist community (30). In the present study, all patients with diagnosed EPI received PERT, with subsequent improvement in abdominal symptoms, suggesting that they were related to pancreatic dysfunction instead of SSA AEs or syndromes related to functioning tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PERT is, therefore, useful to treat malnutrition in PDAC patients affected by PEI, and is associated with an improvement in QoL and survival[ 127 ]. Nevertheless, the optimal dose and optimal timing of PERT administration in PDAC patients is not well defined[ 128 ]. A very recent position paper by Pezzilli et al [ 12 ] aimed to give recommendations on PERT in the PDAC setting, concluding that patients with head PDAC should be given enzymes, while a diagnostic evaluation should be performed using fecal elastase in patients affected by body or tail neoplasm prior to giving them PERT.…”
Section: Nutritional Managementmentioning
confidence: 99%